Territorialidade e manejo cultural da piaçava pelo Povo Werekena -Terra Indígena Alto Rio Negro/AM - Diego Ken Osoegawa; Ivani Ferreira de Faria (Confins)
The Werekena people for decades went through the process of exploitation in a relationship of slavery in which piassava was the primary instrument. They were seen as mere resources (commodities), disregarding the importance of piassava as a cultural element present in both the socio-biodiversity and territoriality of these people. The article aims to demonstrate the relationship between the cultural management of piassava and the territoriality of the Werekena people, inhabitants of the Xié River/AM. Methodological procedures of participatory research were used with fieldwork through knowledge management workshops, participant mapping (participant cartograms), techniques of sensitive listening, mediation and photographic records in addition to secondary data collections to analyze the problem. Piassava management and art-making activities express the identity of the Werekena people and their process of territorialization in the region, manifested in cultural management, which resisted commercial extractivism and slave labor relations, and which can be observed, in the extraction not commercial use of this element and in the production of artifacts and crafts for family use. These factors show the relevance of piassava as one of the activities to integrate the corporate project of the people of the Xié River and the potential to support the historical process that has been taking place to expand autonomy.